Yield of Pleurotus and Agaricus on mycorrhiza-inoculated castor and mulberry biomass - Sharma, Satyawati; Kashyap, Suman; Singh, Anshu; Chaudhry, P N; Vasudevan, Padma (Mushroom Research, 2015)
Please see the full text